Multivitamin Supplements Have No Effect on Growth of Tanzanian Children Born to HIV-Infected Mothers(1)(2)(3)(4) - Kupka, Roland (American Society for Nutrition, 2013)
Growth faltering and micronutrient deficiencies commonly coexist in HIV-exposed children in sub-Saharan Africa, and correcting deficiencies, such as those of vitamins B-complex, C, and E, may improve HIV-related endpoints and child growth. We therefore examined the effect of daily oral supplementation of vitamins B-complex, C, and E on growth among 2341 children born to HIV-infected mothers in Tanzania. HIV-infected women pregnant at ≤32 wk of gestation were enrolled in the study. Children were randomized at age 6 wk to receive multivitamins or placebo until age 104 wk. All women received the same types of vitamins pre- and postnatally. At 6 wk, 256 children (11.1%) were HIV infected and the mean (SD) Z-scores for length for age (LAZ), weight for length (WLZ), and weight for age (WAZ) were −0.39 ± 1.20, −0.21 ± 1.23, and −0.52 ± 1.11, respectively. There was no overall treatment effect on LAZ, WLZ, or WAZ profiles during the follow-up (P ≥ 0.15). There was no treatment effect from 6 to 104 wk on LAZ [(95% CI: −0.14, 0.13); P = 0.94], WLZ [(95% CI: −0.17, 0.13); P = 0.78], or WAZ [(95% CI: −0.15, 0.16); P = 0.97] or on the incidence of growth failure, defined as respective Z-scores < −2 (P ≥ 0.29). Among the subgroup of HIV-uninfected children, there was no treatment effect from 6 to 104 wk on LAZ, WLZ, and WAZ (P ≥ 0.71) or on the incidence of growth failure (P ≥ 0.16). Multivitamin supplements had no effect on growth among children born to HIV-infected women who were themselves receiving multivitamins.